Faktor-Faktor yang Berhubungan dengan Persepsi Masyarakat terhadap Vaksin-19 di Kelurahan Remu Sorong, Papua Barat - Imah Oktavia; Margaretha Juita Iriayanti; Jovan Alvendo Iek; Muhammad Faizal Arianto (Yayasan Literasi Sains Indonesia, 2024)
Corona virus or corona virus is part of a large family of viruses that can cause infections in the upper respiratory tract with mild and moderate levels. The corona virus, also known as the novel corona virus (nCoV), was first discovered in the city of Wuhan, China in November 2019. Corona Virus Disease 2019 (COVID-19) has been declared a global pandemic by the World Health Organization (WHO). Internal factors: feelings, attitudes and individual character, desires or expectations, prejudices, learning, attention (focus), physical condition, mental disorders, values, and needs as well as interests and motivation. External factors: family background, knowledge, information obtained and the needs of the surroundings, intensity, size, repetition of movements, resistance, new and familiar or unfamiliar objects. Efforts are needed to educate the public about the importance of vaccination and overcome problems that arise. Apart from that, education level and age also influence people's perceptions of vaccination. People who are more educated and older tend to have a more positive perception of vaccination, so there needs to be a special strategy that targets younger and less educated groups of people.